Detection of human coronavirus 229E in nasal washings using RNA:RNA hybridization - Myint, S. (J Med Virol, 2005)
A method is described for the detection of human coronavirus 229E (HCV 229E) in nasal washings using RNA:RNA filter hybridization. Volunteers were inoculated with HCV 229E, and daily nasal washings were collected. These washings were then examined for the presence of viral RNA using a single‐stranded RNA probe. Nucleic acid hybridization is shown to be a sensitive technique for the diagnosis of HCV 229E infections.